Values of farmers: Evidence from Germany - Viktoria Graskemper; Jan-Henning Feil (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2021)
Against the background of fundamentally changing political and social requirements of agricultural production, the requirement profile of farmers has changed. The future of agriculture is widely discussed. To prepare a ground for future debates and policy programme design, it is essential to get an understanding of which values underlie farmers' behaviour. This paper applies SCHWARTZ' value theory to a large quantitative survey (N = 787) of German farmers. Next to the overall value portrait, different value portraits within the sample of farmers are analysed. Farmers of the sample first and foremost prioritise self-transcendence values followed by openness to change. Conservation and self-enhancement are ranked to be less important within farmers' value priorities. Furthermore, three different value portraits are identifiable within the sample. These groups differ significantly among other things in their risk attitude and involvement in structural diversification. Implications for agricultural policy design and agricultural management are derived from the results.
Keywords: 330; farmer values; PVQ; agricultural values; entrepreneurship